Disaster vulnerability by demographics? - Ilan Kelman (The White Horse Press, 2020)
This article provides a brief overview of the relationship between disaster vulnerability and demographic variables. Population numbers and densities are examined along with using a gender focus as illustrative of individual characteristics. For the most part, people’s and society’s choices create vulnerabilities based on demographics rather than specific demographic characteristics inevitably conferring vulnerability.